Предмет: Алгебра,
автор: ledimilena1
помогите, пожалуйста!
вычислите значение выражения (x^3 - x^2 - 6x) / (x^2 - 4), при x 2,25.
Ответы
Автор ответа:
0
(x^3-x^2-6x)/(x^2-4)= x(x^2-x-6)/(x-2)(x+2)
Решим квадратное уравнение:
x^2-x-6=0
a=1 b=-1 c=-6
D=1+24+=25
x1=3
x2=-2
x(x-3)(x+2)/(x-2)(x+2)=x(x-3)/x-2=2.25(2.25-3)/2.25-2=2.25(-0.75)/0.25=-6.75
Решим квадратное уравнение:
x^2-x-6=0
a=1 b=-1 c=-6
D=1+24+=25
x1=3
x2=-2
x(x-3)(x+2)/(x-2)(x+2)=x(x-3)/x-2=2.25(2.25-3)/2.25-2=2.25(-0.75)/0.25=-6.75
Похожие вопросы
Предмет: Русский язык,
автор: danyamiloxin
Предмет: Алгебра,
автор: raspopovveniamin
Предмет: Математика,
автор: yankaa51
Предмет: Информатика,
автор: lapshina1982